Peningkatan Proliferasi Limfosit Limpa pada Tikus yang Diberi Makan Sorgum (THE INCREASE OF SPLEEN LYMPHOCYTES PROLIFERATION IN SPRAGUE DAWLEY RATS THAT WERE FED SORGHUM DIETS) - Puspawati, Gusti Ayu Kadek Diah; Rungkat, Fransiska Zakaria (Jurnal Veteriner, 2012)
Sorghum is a cereal crop that could be use as an alternative source in food diversification strategy. Ithas high carbohydrate content similar to rice. Its protein content is higher than that of rice and this crophas the potential to be produce in increasing quantities in Indonesia. Nowadays, the demand of foodindustry is not only concern for nutritious food but also for health benefits. Several research reports haveshowed that sorghum contains bioactive compounds that are beneficial to human health such as in decreasingthe risk of degenerative diseases. In vitro studies have shown that this cereal crop has the capacity toincrease lymphocytes proliferation. The objective of this study is to study the biological potency of sorghumin lymphocytes cell proliferation in rats. Rats were grouped into three: i) control group animals; ii) animalswere fed 100% of sorghum diets, and iii) animals were fed 50% of sorghum diets. The results showed thatan increase in lymphocytes cells proliferation activity by 63% and 70% were seen in animals that were fed100% and 50% sorghum diets, respectively.
Keywords: sorghum, proliferation lymphocyte, rats